The Effect of Planning and Supervision on Performance of Employees at the Health Department of Bogor City - Budi Safari; Indri Astuti; Eka Permana (Green Publisher Indonesia, 2022)
The purpose of this study was to determine how much influence planning and supervision had on the performance of employees at the Bogor City Health Office, either partially or simultaneously. The research method used is a survey. Ary, Yacobs and Razavich stated that the survey method was designed to obtain information about the status of symptoms at the time the research was conducted with the aim of describing what variables or conditions or conditions existed in a situation. The data needed in this study is data regarding employee perceptions of the influence of Planning and Supervision that have an impact on employee performance. The sampling technique used is based on the provisions of random sampling, where a sample of 50 people is taken from a population of 124 people. The result of this research is that planning and monitoring both partially and simultaneously have a significant positive effect on the performance of the Bogor City Health Office employees.